2010
DOI: 10.1159/000322082
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Expression, Activity and Nuclear Localization of Prolyl Oligopeptidase Protein in the Developing Rat Brain

Abstract: Prolyl oligopeptidase (POP) is a serine protease that hydrolyzes peptides shorter than 30-mer. Some evidence has recently been obtained that POP can generate protein-protein interactions and therefore participate in various physiological and pathological events. Several studies have reported that POP may be involved in neurogenesis since its activity increases during development and can be found in the nucleus of proliferating tissues. In cell cultures, POP has been shown to be localized in the nucleus, but on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…This role of POP was first suggested by the finding that a specific POP inhibitor, ZTTA, inhibited DNA synthesis in the cultured cells of flesh fly and mouse and POP was localized to the nuclei in the cells (Ishino et al, 1998;Ohtsuki et al, 1997). Some of the recent studies also support this function by showing that POP was localized to the nucleus in proliferating or differentiating cells (Hannula et al, 2010;Moreno-Baylach et al, 2008). However, no particular mechanisms have yet been suggested, so it may also be possible that the cytoplasmic and membrane-associated POP could participate in cell cycle regulation.…”
Section: Molecular Mass Of Popmentioning
confidence: 83%
See 1 more Smart Citation
“…This role of POP was first suggested by the finding that a specific POP inhibitor, ZTTA, inhibited DNA synthesis in the cultured cells of flesh fly and mouse and POP was localized to the nuclei in the cells (Ishino et al, 1998;Ohtsuki et al, 1997). Some of the recent studies also support this function by showing that POP was localized to the nucleus in proliferating or differentiating cells (Hannula et al, 2010;Moreno-Baylach et al, 2008). However, no particular mechanisms have yet been suggested, so it may also be possible that the cytoplasmic and membrane-associated POP could participate in cell cycle regulation.…”
Section: Molecular Mass Of Popmentioning
confidence: 83%
“…In fact, a very recent report showed that POP was localized to the nucleus only early in the brain development (Hannula et al, 2010). Although there is no conclusive evidence for the nuclear POP controlling the cell cycle, it is widely accepted that POP plays some important roles in development and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, it is expressed in a wide variety of tissues, including the ovary, brain, liver, testis, kidney, thymus, breast, stomach, prostate gland, and spleen (Goossens, De Meester, Vanhoof, & Scharpé, ; Myöhänen, Pyykkö, Männistö, & Carpen, ). POP participates in the regulation of a comprehensive range of physiological or pathological processes by affecting cell proliferation (Matsubara, Ono, Tsubuki, Irie, & Kawashima, ; Suzuki, Sakaguchi, Tanaka, Yoshimoto, & Takaoka, ), differentiation (Hannula, Mannisto, & Myohanen, ; Matsubara et al, ), apoptosis (Matsuda, Sakaguchi, Tanaka, Yoshimoto, & Takaoka, ), and hydrolyzing extracellular polypeptides (Matsuda et al, ). In the central nervous system, POP plays an important role in learning and memory.…”
Section: Introductionmentioning
confidence: 99%
“…In the mature healthy brain, PREP is highly expressed in a certain group of neurons in well-defined areas such as the striatum, cortex, hippocampus and cerebellum but scarcely detectable in glial cells [ 13 , 14 ]. PREP has been associated to neurodegeneration [ 10 , 11 ], proliferation [ 15 ], neuronal differentiation [ 16 ], development [ 17 , 18 ] and also to inflammation [ 19 21 ]. PREP levels have been found altered in Alzheimer’s (AD), Parkinson’s (PD) [ 22 ] and Huntington’s (HD) diseases (reviewed in [ 10 ]).…”
Section: Introductionmentioning
confidence: 99%